If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(-9) = 4x + 2x Reorder the terms for easier multiplication: -9F = 4x + 2x Combine like terms: 4x + 2x = 6x -9F = 6x Solving -9F = 6x Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Divide each side by '-9'. F = -0.6666666667x Simplifying F = -0.6666666667x
| (3x+4)x(5x+10)=50 | | -8+2y=-12 | | (7x-3)= | | 3x+44=83 | | (100x^2)-(60x)+(9)=0 | | H^2+10h=-22 | | 2(7y+1)+13=51+8(y-9) | | log81x=3/4 | | 7(2x+3)=1+2(8x+7) | | -8x+10(x-10)=36 | | -2(g+9)=0 | | 6/x=13/9 | | -4x+5=6x-75 | | 8(-3)=-48 | | 3(u-13)=15 | | 9(7x-8)+6=4x+2 | | 3(r+-7)+16=10 | | -5+5t=40 | | 3x^2-4=367 | | 1=2(p+9)-9 | | 2(g+1)-5=3 | | 10-1/2x6 | | 7x+10=-3x-17 | | -2(w+7)+17=11 | | X-(-4)/6=-5 | | 4x/2=1715 | | 2750=25(9+35) | | -1+5=2(-5+1) | | 18x/45 | | 5+5=2(10+1) | | 18=45 | | 10/52=x/25 |